Capping Actin Protein Overexpression in Human Colorectal Carcinoma and Its Contributed Tumor Migration. (1st August 2018) - Tsai, Tsung-Jung; Lim, Yun-Ping; Chao, Wen-Ying; Chen, Chien-Chin; Chen, Yi-Ju; Lin, Ching-Yen; Lee, Ying-Ray
Abstract : Objective . Human colorectal cancer (CRC) is the third most common cancer; patients with metastatic colorectal cancer (mCRC) show poor prognosis than those with CRC cases. There are no reliable molecular biomarkers for the diagnosis of CRC prognosis except with pathological features. Therefore, it is urgent to develop a biomarker for diagnosis and/or prediction of human CRC. In addition, capping actin protein (CapG) belongs to the gelsolin family and has been reported to contribute on tumor invasion/metastasis in multiple human cancers. Here, we are the first to evaluate the expression of CapG in human CRCs. Study Design . To investigate the expression levels of CapG in human tissue array by immunohistochemistry (IHC) staining. Moreover, the mRNA and protein levels were also confirmed in four CRC cell lines and determined using real-time RT-PCR and Western blotting. Finally, a Matrigel transwell invasion assay was used to evaluate the invasion ability in CapG high or low expression cells. Results . We demonstrated that CapG could be determined in the normal colon tissue and human CRC specimens. However, CapG was significantly overexpressed in the mCRC specimens compared with that in CRC specimens and normal cases. It was also detectable in the four CRC cell lines including mRNA and protein levels. We also found that knockdown of the expression of CapG reduced tumor migration. Conclusions . In this study, we suggested that CapG could be used as a biomarker for metastatic CRC in the clinical specimens. Moreover, our in vitro study demonstrated that CapG might contribute on tumor metastasis in human CRCs.